Impact of Artificial Intelligence on Corporate Governance and Board Decision-Making in the Digital Era (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Business concerns are being forced by digital technology to update their current business strategies and create fresh ones that combine cutting-edge concepts in order to meet modern demands. Due to the popularity of the "Go digital" idea, businesses have transformed into inventive machines that focus more on the "Eco system" style of governance. In a networked world, innovative and nimble businesses are well-prepared and constantly adapting their plans to fit the needs of the moment, but established businesses encounter a significant disconnect between their governance strategy and their operational requirements. The businesses that have historically performed the best in the market face numerous problems as a result of fast-moving, technology-driven markets.This conceptual paper aims to provide an overview of the potential available to companies in the digital era as well as the problems and difficulties that may arise. The paper's main goal is to highlight the opportunities and problems that Corporations and Companies face in the digital era and to identify the areas where their governance practices need to change. The theoretical information in the study is based on secondary data that was gleaned from a variety of sources, including text books, newspapers, journals, and online sources.